Estimates of accuracy and time consuming on the digital modeling of the characteristics of dynamic systems using the properties of the integral of convolution - Іванова, Л. М. (Proceedings of National Aviation University (archive), 2021)
An approach to constructing a digital model of a dynamic system using the properties of a convolution integral, an approach to assessing the accuracy of the functioning of the constructed model is considered. For a digital model constructed using the proposed approach, the maximum relative accuracy of simulation 6 and the time consumption of simulating a single point of the reaction